2014
DOI: 10.1111/chd.12220
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Congenital Heart Disease in India

Abstract: The prevalence of CHDs in our cohort was high, possibly because of the power of the diagnostic methods we used and the inclusion of all age groups. Adults with CHDs may significantly contribute to the prevalence of CHDs in the next generation, and this needs to be considered when estimating prevalence rates. Although several small regional studies have been carried out in India, there is an urgent need to establish a nationwide registry/database for congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 28 publications
4
38
2
3
Order By: Relevance
“…Here CAD and pericardial diseases predominated. The findings in our study is in contrast with work done by Fahid et al where he demonstrated that the incidence of cardiac surgery tends to show increasing number among the elderly with CABG being the common procedure [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Here CAD and pericardial diseases predominated. The findings in our study is in contrast with work done by Fahid et al where he demonstrated that the incidence of cardiac surgery tends to show increasing number among the elderly with CABG being the common procedure [25].…”
Section: Discussioncontrasting
confidence: 99%
“…It has increased steadily since 1930. The birth prevalence since 1995 ranges between 1.9 and 9.3/1000 births [4], [5], [8]. The current lower prevalence in Africa is similar to that in the West in the early 1930s (0.6/1000 births) and is probably related to an under diagnosis.…”
Section: Introductionmentioning
confidence: 92%
“…Congenital heart disease (CHD) and early acquired heart disease (EAHD) are of special importance in adolescents as they may impact their subsequent health as they age [2], [3]. Many studies which investigated the prevalence of CHD in fetal and newborn populations found fewer subjects than in population studies of older children and adolescents [4], [5]. Echocardiographic screening revealed a prevalence rate of approximately 3.5% for cardiac lesion in older children [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…последнее десятилетие большинство авторов сходятся во мнении, что частота врожденных по-роков сердца (согласно МКБ-10 Q 20 -Q 28 ) варьирует от 19 до 75 на 1000 родившихся живыми [1][2][3], при этом тяжелые врожденные пороки регистрируются с часто-той 19,1-23,9 на 1000 рождений [4]. Большое значение в диагностике и определении генеза пороков сердца имеют фетальная и постнатальная эхокардиография, клинические и генетические методы исследования [4].…”
unclassified